1970
DOI: 10.1021/jm00298a032
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and antiinflammatory activity of some aryltetrazolylalkanoic acids

Abstract: brate has no significant effect on mouse serum cholesterol under these conditions. Although the mechanism of action of l19 has not been elucidated, it does not appear to have any significant effect on the incorporation of mevalonate into cholesterol.(19) The generic name of 1, formerly designated DH 581, is probucol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

1970
1970
1992
1992

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…It is interesting to examine how these operational schemes might have worked out in practice. The first example is based on the work of Buckler,et al,4 concerning the antiinflammatory activity of a series of substituted aryltetrazolylalkanoic acids. Of some 28 compounds synthesized which differed only in the type of substitution of the 5-aryl function, 8 are listed in Table II in the order indicated for synthesis by following the operational scheme given in Scheme I.…”
Section: Utilization Of Operational Schemes For Analog Synthesis In D...mentioning
confidence: 99%
“…It is interesting to examine how these operational schemes might have worked out in practice. The first example is based on the work of Buckler,et al,4 concerning the antiinflammatory activity of a series of substituted aryltetrazolylalkanoic acids. Of some 28 compounds synthesized which differed only in the type of substitution of the 5-aryl function, 8 are listed in Table II in the order indicated for synthesis by following the operational scheme given in Scheme I.…”
Section: Utilization Of Operational Schemes For Analog Synthesis In D...mentioning
confidence: 99%
“…remaining metaand dimeta-substituted phenyltetrazolylpropionic acids gave eq 6. This is significant at the 99.95% r n s log AI = -0.22it2 + 0.42 + 0.61 0.697 33 0.27 (3) log AI = -0.22 2 + 0.42 -0.06am + 0.62 0.701 33 0.27 (4) log AI = -0.30 2 + 0.56 + 0.62 0.860 18 0.25 (5) log AI = -0.37 2 + 0.58ff + 0.63 0.945 16 0.16 (6) log AI = -0.1 2 + 0.19ff + 0.61 0.427 15 0.26 (7) log AI = -0.14 2 + 0.23 + 0.66 0.609 14 0.20 (8) log AI = -0.85 + 0.77am + 0.58 0.841 14 0.14 (9) log AI = -0.31 2 + 0.48ff + 0.73 0.851 28 0.20 (10) log AI = -0.24om + 0.21…”
mentioning
confidence: 97%
“…It is not. However, if the free energy of such an interaction were small relative to the total drugreceptor interaction, it could be masked by the electrical component of the term already present in the equations.1, 5,18 And, if this is the case, the activities of compounds whose substitutents have similar it values but different o values should be distinctly different. In every case the deactivating substitutent is the more active compound.…”
mentioning
confidence: 99%
“…Some time ago, we found that certain substituted (5phenyl-2-tetrazolyl)propionic acids I possessed high levels /-\ N=N l'N-Z 'N-' Nx-v/x'"COOH of antiinflammatory activity. 2 The geometrical isomers II and III, which have the phenyl and the propionic acid groups attached to adjacent ring atoms, were inactive. This led us to conclude that the linear geometry of I was necessary for activity.…”
mentioning
confidence: 99%